2009
DOI: 10.1098/rspb.2009.1256
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of weaponry in female bovids

Abstract: Weaponry is ubiquitous in male ungulates and is driven by intrasexual selection, but the mystery surrounding its sporadic presence in females remains unsolved. Female horns are often smaller and shaped differently to male horns, suggesting a different function; indeed, hypotheses explaining the presence of female horns include competition for food, male mollification and defence against predators. Here we use comparative phylogenetic analyses to show that females are significantly more likely to bear horns in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
100
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(104 citation statements)
references
References 34 publications
2
100
0
Order By: Relevance
“…In addition, our laboratory experiment with naïve domestic chicks confirms the suggestion that predators' wariness of eyespots is effectively innate (4,10), yet this unlearned wariness is conditional on both caterpillars' bodies and eyespots being large. More broadly, our results provide important support for the growing body of evidence suggesting that the evolution of antipredator adaptations is closely tied to other prey traits, such as body size and habitat use (25,(34)(35)(36)(37)(38)(39).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…In addition, our laboratory experiment with naïve domestic chicks confirms the suggestion that predators' wariness of eyespots is effectively innate (4,10), yet this unlearned wariness is conditional on both caterpillars' bodies and eyespots being large. More broadly, our results provide important support for the growing body of evidence suggesting that the evolution of antipredator adaptations is closely tied to other prey traits, such as body size and habitat use (25,(34)(35)(36)(37)(38)(39).…”
Section: Discussionsupporting
confidence: 73%
“…There is now abundant empirical evidence indicating that the efficacy of various antipredator adaptations is influenced by both prey size (35,48) and the habitats in which prey are found (49,50). A number of comparative phylogenetic studies also have established links between prey ecology and defensive strategy; for example, conspicuous warning signals are selected in Papilio caterpillars only if they inhabit narrow-leaved plants in which it is difficult to hide (51), whereas the possession of weaponry (i.e., horns) in female bovids is related to large body size and living in open habitats, both of which increase conspicuousness (52). Similar analyses have shown that small species tend to invest more in camouflage compared with large species (53), and that selection for mimetic fidelity increases with body size (25).…”
Section: Discussionmentioning
confidence: 99%
“…The evolution of female weaponry has been explored in other taxa, with the prevailing conclusion being that these traits are under natural selection (Kiltie 1985;Stankowich & Caro 2009). However, this conclusion may be due to that fact that the concept of intrasexual selection is often applied restrictively, only considering competition for 'mating' opportunities (Andersson 1994), when in fact selection acts on traits of both sexes involved in competition for 'reproductive opportunities', including competition for 'mating' and 'breeding'.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the most common forms of female-female territorial competition in ungulates involve the defence of offspring from infanticidal females, and the defence of food for offspring long after matings have occurred [92]. Comparative analyses provide further evidence that female weapons have evolved in this diverse group via competition for ecological resources associated with fecundity, rather than for mates [11].…”
Section: Review Of Empirical Studiesmentioning
confidence: 99%